EFFECT OF WORK SKILLS ON EMPLOYEE PERFORMANCE CV. OSANO SCREEN PRINTING AND EMBROIDERY THROUGH WORK EXPERIENCE - Sanusi Silitonga, Eddy (Dinasti International Journal of Management Science, 2022)
This study aims to determine employee performance is influenced by work skills directly or indirectly through work experience as an intervening variable in CV Osano Sablon and Embroidery. The method used in this research is a quantitative approach method carried out through surveys, observations, and interviews. The results in research and analysis based on the intervening or mediation test show that the value of the indirect effect through work experience is greater than the value of the direct influence of work skills on employees' performance. With these results, it can be concluded that the work experience variable can be a variable that mediates the effect of work skills on employee performance in CV. Osano Screen Printing and Embroidery.